Review and Progress towards the Common Broadband Management of High-Voltage Transmission Grids: Model Expansion and Comparative Modal Analysis. (27th December 2012) - Lazaropoulos, Athanasios G.
Abstract : The need of bridging the digital gap between underdeveloped/developed areas and promoting smart grid (SG) networks urges the deployment of broadband over power lines (BPL) systems and their further integration. The contribution of this paper is fourfold. First, based on the well-established hybrid model of (Lazaropoulos and Cottis 2009, 2010, Lazaropoulos, 2012) and the generic multidimensional network analysis tool presented in (Lazaropoulos 2012, Sartenaer 2004, Sartenaer and Delogne 2006, 2001) an exact multidimensional chain scattering matrix method, which is suitable for overhead high-voltage/broadband over power lines (HV/BPL) networks, is proposed and is evaluated against other theoretical and experimental proven models. Second, the proposed method investigates the overhead HV/BPL transmission grids (overhead 150 kV single-circuit, 275 kV double-circuit, and 400 kV double-circuit multiconductor structures) with regard to their end-to-end signal attenuation. It is found that the above features depend drastically on the overhead power grid type, the frequency, the MTL configuration, the physical properties of the cables used, the end-to-end distance, and the number, the length, and the terminations of the branches encountered along the end-to-end BPL signal propagation. Third, the impact of the multiplicity of the branches at the same junction in overhead HV grids is first examined. Based on the inherent long-branch structure and the quasi-static behavior of single/multiple branches with matched terminations of overhead HV grid, a simple approach suitable for overhead HV/BPL channel estimation is presented. Fourth, identifying the similar characteristics among different overhead HV/BPL configurations, an additional step towards the common overhead HV/BPL analysis is demonstrated; the entire overhead HV/BPL grid may be examined under a common PHY framework regardless of the overhead HV/BPL grid type examined. Finally, apart from the presentation of broadband transmission potential of the entire overhead transmission power grid, a consequence of this paper is that it helps towards: (i) the better broadband monitoring and management of overhead HV transmission power grids in an interactive SG network; and (ii) the intraoperability/interoperability of overhead HV/BPL systems under the aegis of a unified transmission/distribution SG power network.